2022
DOI: 10.1177/1934578x221113707
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity and Structure-Activity Relationships of Resveratrol and its two Natural Analogs, 4,4′-Dihydroxystilbene and Pinosylvin

Abstract: Resveratrol (RES) and its two natural analogues, 4,4′-dihydroxystilbene (DHS) and pinosylvin (PIN), are very important polyphenols and have attracted considerable pharmaceutical interest because of their diverse biological activities. However, their adverse effects on motor nerves and glioma cells have not been properly assessed. Herein, we surveyed the toxicity and analyzed the structure-activity relationship of these three polyphenols using transgenic zebrafish ( Danio rerio) and U87. Results indicated that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…proach in a practical application, we studied the drug effects of its analogue 3k [(E)-1,3-dimethoxy-5-styrylbenzene] in accordance with a previous report. 10 The test results showed that treatment of zebrafish embryos with 3k (0.01-1 g/mL) led to a significant neurosuppressive effect (Figure 1), suggesting that 3k might be developed as a potential nerve-growth inhibitor. Additional experiments were performed to gain insight into the reaction mechanism.…”
Section: Letter Synlettmentioning
confidence: 98%
See 1 more Smart Citation
“…proach in a practical application, we studied the drug effects of its analogue 3k [(E)-1,3-dimethoxy-5-styrylbenzene] in accordance with a previous report. 10 The test results showed that treatment of zebrafish embryos with 3k (0.01-1 g/mL) led to a significant neurosuppressive effect (Figure 1), suggesting that 3k might be developed as a potential nerve-growth inhibitor. Additional experiments were performed to gain insight into the reaction mechanism.…”
Section: Letter Synlettmentioning
confidence: 98%
“…We then screened a range of reaction temperatures to identify the optimal temperature. Control experiments showed that when the reaction temperature reached 120 °C, the conversion rate of the alkyne reached 100%, and when the reaction temperature was below 120 °C, the conversion rate was lower (entries [10][11][12]. These results show that 120 °C is the optimal temperature.…”
Section: Letter Synlettmentioning
confidence: 99%